Мезолітичні витоки перших індоєвропейських культур Європи за даними археології - Залізняк, Л.Л. (Археологія, 2016)
У статті розглянуто спільне мезо-неолітичне підґрунтя найдавніших індоєвропейських культур України (Маріуполь, Середній Стіг) та Центральної Європи (культура лійчастого посуду, кулястих амфор) IV тис. до н. е. Археологічні матеріали свідчать, що спільний культурно-генетичний субстрат найдавніших індоєвропейців Європи сформувався в VI—V тис. до н. е. внаслідок міграції на схід мезолітичної людності Західної Балтії через територію Польщі та Полісся до Середнього Дніпра й далі до Сіверського Дінця. The author of the article makes an attempt to reconstruct the cultural and genetic origins of the first Indo-Europeans in Europe at the end of the Stone Age with help of archaeological materials. It is about the single Meso-Neolithic real of the ancient Indo-European cultures in Ukraine (Mariupol and Seredniy Stih) and in Central Europe (Funnelbeaker culture) in the 4th millennium BC. The archaeological, anthropological, and hydronymic data evidence that in the lowlandsfrom the Lower Rain at the west to the Middle Dnipro and Siverskyi Donets Rivers at the east, at the end of the Mesolithic, an ethno-cultural community existed which probably participated in the development of ancient Indo-Europeans of Europe as their genetic substrate. The latter developed in the 6th and 5th millennia BC as a result of migration of Western Baltic Mesolithic population to the east via the territory of Poland and Polissya to the Dnipro River middle region and further to the Siverskyi Donets. Such waves of largescale migrations periodically moved from Central Europe by Middle European lowlands far to the east since the Final Palaeolithic. Автор статьи делает попытку реконструкции с помощью археологических материалов культурно-генетических истоков первых индоевропейцев Европы конца эпохи камня. Идет речь о единой мезо-неолитической подоснове древнейших индоевропейских культур Украины (Мариуполь, Средний Стог) и Центральной Европы (культура воронковидных кубков) IV тыс. до н. э. Данные археологии, антропологии и гидронимики свидетельствуют, что на низменностях от Нижнего Рейна на западе до Среднего Днепра и Северского Донца на востоке в конце мезолита существовала этнокультурная общность, которая, вероятно, приняла участие в формировании древнейших индоевропейцев Европы в качестве их генетического субстрата. Последний сложился в VI—V тыс. до н. э. вследствие миграции мезолитического населения Западной Балтии на восток через территорию Польши и Полесья на Средний Днепр, и далее до Северского Донца. Подобные волны масштабных миграций периодически катились с Центральной Европы Среднеевропейскими низменностями далеко на восток начиная с финального палеолита.